Pengaruh Pendidikan dan Pelatihan, Insentif Finansial, dan Lingkungan Kerja Fisik Terhadap Kinerja - Astrayana, Komang Tribayu; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen, 2014)
Performance is work result/work achievement that attained by employee by doing task that adapted with responsibility and their roles in the company, then it can reach organization’s goal. The purpose of this research is to know the effect of education and training, financial incentive, and physical work environment. BAPPEDA Kabupaten Buleleng with respondent amount is 80 employees. Data analysis technique that was used to test hypothesis is couple linear regression analysis, classic assumption test, simultaneous regression test, partial regression test that have purpose to know the  simultaneous and partial effect and also use standardized coefficients beta to determine dominant variable that affect employee’s performance. Based on the analysis result, education and training variable, financial incentive, and physical work environment is has significant effect partially to BAPPEDA employee’s performance with financial incentive variable as variable that has dominant effect to employee’s performance, is expected to notice education and training, financial incentive, and physical work environment so it can increase employee’s performance so it can reach goals set.
Keywords: performance, education and training, financial incentive, and physical work environment